Information Support of Cost Audit in Construction Organizations - Yusupova Farizabonu Zarifovna (Universitas Muhammadiyah Sidoarjo, 2023)
This article presents the border between the items of expenses of construction enterprises and their various combinations, as well as the possibilities of showing the results of the works of construction entities, and explains the accounting and description of the income from the subsequent financial and economic activities of the expenses. Information sources of costs are studied.